Expectation values of coherent states for SU(2) Lattice Gauge Theories - Liegener, Klaus; Zwicknagel, Ernst-Albrecht (Journal of High Energy Physics, 2020)
This article investigates properties of semiclassical Gauge Field Theory Coherent States for general quantum gauge theories. Useful, e.g., for the canonical formulation of Lattice Gauge Theories these states are labelled by a point in the classical phase space and constructed such that the expectation values of the canonical operators are sharply peaked on said phase space point. For the case of the non-abelian gauge group SU(2), we will explicitly compute the expectation value of general polynomials including the first order quantum corrections. This allows asking more precise questions about the quantum fluctuations of any given semiclassical system.
CRIS-Team Scopus Importer:2020-02-18
Keywords: Beyond Standard Model; Gauge Symmetry; Lattice Quantum Field Theory; Nonperturbative Effects